2001
DOI: 10.1177/026765910101600208
|View full text |Cite
|
Sign up to set email alerts
|

Is compartment pressure related to plasma colloid osmotic pressure, in patients during and after cardiac surgery?

Abstract: Haemodilution is always considerable during cardiopulmonary bypass (CPB). If this extra fluid sits in the muscle compartments then a corresponding rise in the compartment pressure (CP) is to be expected. The aim of this study was to measure pressure changes in a body compartment with new equipment, the MTC (Microtransducer). Changes in plasma colloid osmotic pressure (COP) were also measured during and after CPB to find a connection, if any, between CP and plasma COP. Ten elective consecutive CPB patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There were several trials on the influence of colloid oncotic pressure (COP) on CPB and renal function showing conflicting results [9][10][11][12][13]. Therefore, using human albumin to increase oncotic pressure is not practised regularly [1].…”
Section: Introductionmentioning
confidence: 99%
“…There were several trials on the influence of colloid oncotic pressure (COP) on CPB and renal function showing conflicting results [9][10][11][12][13]. Therefore, using human albumin to increase oncotic pressure is not practised regularly [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that the pressure in a closed muscle compartment rises significantly during and after cardiopulmonary bypass (CPB) and remains increased up to 48 h. 1 We assumed that the inflammatory response and edema causes the pressure changes in the compartment.…”
Section: Introductionmentioning
confidence: 98%